2015
DOI: 10.5539/gjhs.v7n6p170
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Interdisciplinary Collaboration Models and Frameworks From Similarities to Differences: A Systematic Review

Abstract: Introduction:So far, various models of interdisciplinary collaboration in clinical nursing have been presented, however, yet a comprehensive model is not available. The purpose of this study is to review the evidences that had presented model or framework with qualitative approach about interdisciplinary collaboration in clinical nursing.Methods:All the articles and theses published from 1990 to 10 June 2014 which in both English and Persian models or frameworks of clinicians had presented model or framework o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
0
18
0
3
Order By: Relevance
“…However, members of a team cultivate trust by working together over time. Mahdizadeh et al [32] noted that trust among nurses and physicians at different organizational levels are important in the creation of a professional relationship. Members of the interdisciplinary team share information willingly in an environment where mutual respect and trust are a norm.…”
Section: Trust and Respectmentioning
confidence: 99%
See 3 more Smart Citations
“…However, members of a team cultivate trust by working together over time. Mahdizadeh et al [32] noted that trust among nurses and physicians at different organizational levels are important in the creation of a professional relationship. Members of the interdisciplinary team share information willingly in an environment where mutual respect and trust are a norm.…”
Section: Trust and Respectmentioning
confidence: 99%
“…[12,13,15,22,28,[30][31][32] The loss of trust in a team breeds skepticism among its members. Mistrust impacts negatively on interpersonal relationships making it challenging for team members to work together.…”
Section: Trust and Respectmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of research has shown that IDC is more effective than standard care in terms of clinical outcomes such as improved quality of life and alleviated depressed mood in people with mental disorders-with reducing healthcare costs [1]. Despite advances in research, there is still a lack of conceptual clarity of IDC, resulting in inconsistent models of care and inconsistent findings [2]. The ambiguous conceptualization of IDC impedes the standardisation of evidence-based practice and also limits practical applicability and comparability.…”
Section: Introductionmentioning
confidence: 99%